Smooth Muscle-Targeted Overexpression of Peroxisome Proliferator Activated Receptor-γ Disrupts Vascular Wall Structure and Function - Kleinhenz, Jennifer M. (PLoS One, 2015)
Activation of the nuclear hormone receptor, PPARγ, with pharmacological agonists promotes a contractile vascular smooth muscle cell phenotype and reduces oxidative stress and cell proliferation, particularly under pathological conditions including vascular injury, restenosis, and atherosclerosis. However, pharmacological agonists activate both PPARγ-dependent and -independent mechanisms in multiple cell types confounding efforts to clarify the precise role of PPARγ in smooth muscle cell structure and function in vivo. We, therefore, designed and characterized a mouse model with smooth muscle cell-targeted PPARγ overexpression (smPPARγOE). Our results demonstrate that smPPARγOE attenuated contractile responses in aortic rings, increased aortic compliance, caused aortic dilatation, and reduced mean arterial pressure. Molecular characterization revealed that compared to littermate control mice, aortas from smPPARγOE mice expressed lower levels of contractile proteins and increased levels of adipocyte-specific transcripts. Morphological analysis demonstrated increased lipid deposition in the vascular media and in smooth muscle of extravascular tissues. In vitro adenoviral-mediated PPARγ overexpression in human aortic smooth muscle cells similarly increased adipocyte markers and lipid uptake. The findings demonstrate that smooth muscle PPARγ overexpression disrupts vascular wall structure and function, emphasizing that balanced PPARγ activity is essential for vascular smooth muscle homeostasis.